Engagement, Academic Motivation, and Adjustment of University Students - Cobo-Rendón, Rubia (2022)
Introduction. The entrance of young people to the university is a challenging and important period in their life, both academically and personally. It is required to have a set of skills that allow them to adjust satisfactorily to the demands of the new context. This adjustment process to university life becomes a key variable since it allows facing the motivation, execution, and performance requirements of the university experience in the first years. It is necessary to know those variables that predict an adequate academic adjustment of the students to propose timely improvement interventions. Objective. The objective is to evaluate the predictive capacity of engagement and academic motivation in the adjustment process of university students. Method. Cross-sectional predictive design, and a sample of 512 first-year students from a Chilean university (Male = 297; Female = 215). Average age of 19 years (SD = 1.49). Results. The results reveal that the regression models were statistically significant. Engagement was the highest predictor of academic adjustment (β = .511; p <.01; r2 = .40), institutional (B = .30; p <.01; r2 = .37), social (β = .29; p <.01; r2 = .15) and personal-emotional (β = .30; p <.01; r2 = .10), followed by autonomous motivation. Conclusions. Academic engagement is relevant not only in promoting performance but also in the integration processes of university students. In conclusion, academic engagement and autonomous motivation are predictors of adjustment to university life.